2019
DOI: 10.1186/s12879-019-3967-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with syphilis infection: a cross-sectional survey among outpatients in Asikuma Odoben Brakwa District, Ghana

Abstract: Background Syphilis is a sexually transmitted infection caused by the bacterium Treponema pallidum. The disease affects all ages and both sexes but more prevalent among the sexually active age group of 15–49 years. The purpose of the current study was to determine the prevalence and factors associated with syphilis infection among outpatients 15–49 years in the Asikuma Odoben Brakwa District of Ghana where high levels of infection were earlier reported among antenatal wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Among the risk factors, marital status [P= 0.012; OR= 2.251 (95% CI= 1.206-4.202)] and blood transfusion [P= 0.030; OR= 1.981 (95% CI= 1.083-3.623)] are statistically associated with syphilis among blood donors. These findings also resemble with the results of (Arshad et al, 2016;Halakoto et al, 2017;Banong-le et al, 2019). The culture and norms of not screening the partners for sexually transmitted diseases before marriage leads to transmission of these diseases including syphilis to the married couples.…”
Section: Discussionsupporting
confidence: 86%
“…Among the risk factors, marital status [P= 0.012; OR= 2.251 (95% CI= 1.206-4.202)] and blood transfusion [P= 0.030; OR= 1.981 (95% CI= 1.083-3.623)] are statistically associated with syphilis among blood donors. These findings also resemble with the results of (Arshad et al, 2016;Halakoto et al, 2017;Banong-le et al, 2019). The culture and norms of not screening the partners for sexually transmitted diseases before marriage leads to transmission of these diseases including syphilis to the married couples.…”
Section: Discussionsupporting
confidence: 86%
“…The number of partners and age were not factors associated with syphilis among people in rural areas of Ghana. In this population, significant factors associated with syphilis infection included sub-district of residence, and history of coerced sexual intercourse [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of the cohort used in this study, indicated that gonorrhea, chlamydial, and syphilis infections account for 11.24%, 10.11% and 7.30% of the cases, respectively. Banong-le et al [ 23 ] found the prevalence of syphilis infection among symptomatic patients in a study conducted in Ghana to be 3.2%. This is lower than this study findings (7.30%) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Banong-le et al [ 23 ] found the prevalence of syphilis infection among symptomatic patients in a study conducted in Ghana to be 3.2%. This is lower than this study findings (7.30%) [ 23 ]. Geremew et al [ 21 ] also reported very high prevalence of syphilis (30%) and N .…”
Section: Discussionmentioning
confidence: 99%